A Contribution to the Study of the Integrity Surface of the IC10 Ni3Al-Based Alloy After Creep-Feed Grinding with a Focus on High-Temperature Fatigue Life - Shuaiqi Zhang; Lijie Hu; Zhenyu Yang; Shuxin Niu; Huzi Bao; Qichao Jin; Duoji Renqing; Ruisong Jiang (Metals)
The IC10 directionally solidified superalloy is a nickel-based alloy with high temperature resistance, and its surface integrity has a significant impact on the fatigue life of critical hot-end components in aerospace engines. This paper investigates the influence of creep-feed grinding surface integrity (surface roughness and surface hardness) on the high-temperature fatigue life of IC10 directionally solidified superalloy. High-temperature fatigue life tests were conducted on IC10 directionally solidified superalloy, and a method for evaluating the high-temperature fatigue life of the IC10 directionally solidified superalloy using surface integrity is proposed. The results indicate that as the surface roughness Ra increases from 0.60 μm to 2.15 μm, the maximum valley depth Rv of the grinding surface profile and the stress concentration factor increase, leading to more scratches and wider grooves. The fatigue fracture of IC10 consists of a fatigue source zone, a fatigue propagation zone, and an instantaneous fracture zone. With increasing surface roughness, the number of fatigue sources also increases, and the stress concentration on the grinding surface intensifies. Under the action of multiple fatigue propagation sources, the sample structure is more likely to reach a critical value and lose stability, leading to fracture and thus reducing the high-temperature fatigue life. When the surface hardness increases from 387.11 HV to 393.60 HV, the high-temperature fatigue life of IC10 improves by 68.13%; when the surface hardness increases from 401.62 HV to 418.13 HV, the high-temperature fatigue life of IC10 decreases by 73.12%. The surface integrity of the IC10 directionally solidified superalloy has a notable impact on its high-temperature fatigue life.